Expression of Connexin47 in oligodendrocytes is regulated by the Sox10 transcription factor. - Wegner, Michael; Glaser, Gabriele; et al. (Journal of Molecular Biology, 2006)
In the central nervous system, Connexin32 and Connexin47 are confined to oligodendrocytes where they contribute to myelin formation and maintenance, and are essential for establishing a functional glial syncytium that ensures ionic homeostasis. Despite their importance, not much is known about the regulation of connexin gene expression in oligodendrocytes. Here, we identify group E Sox proteins, in particular Sox10, as essential transcriptional regulators of both connexins. Not only was expression of Connexin32 and Connexin47 severely compromised in spinal cords of mouse mutants with reduced amounts of group E Sox proteins. Sox10 also stimulated in transient transfections the Connexin32 promoter as well as Connexin47 promoter 1b which is the main Connexin47 promoter active in the postnatal spinal cord. Detailed characterization of Connexin47 promoter 1b identified a single monomer binding site that mediated Sox10-dependent promoter activation. The region containing this binding site was also occupied by endogenous Sox10 in 33B oligodendroglioma cells. These results add Connexin47 and Connexin32 to the list of Sox10 target genes and argue that Sox10 may influence transcription of many terminal differentiation and myelination genes in oligodendrocytes as an essential regulatory component of the myelination program. © 2006 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.med.IB.LPCIPDBI.expres
Keywords: HMG; Krox-20; oligodendrocyte; Sox; Sry